Comparative techno-economic assessment of bio-methanol and bio-DME production from oil palm residue. (15th April 2022) - Im-orb, Karittha; Arpornwichanop, Amornchai
Highlights: The bio-MeOH and bio-DME production from oil palm residues is presented. The gasification-MeOH and gasification-DME processes show threshold pinch. The gasification-DME process is more economically feasible. The gasification-MeOH process releases more CO2 . Abstract: The techno-economic assessment was performed to investigate and compare the production of bio-methanol and bio-dimethyl ether (bio-DME) via the combined gasification and chemical synthesis processes (i.e., gasification-methanol (MeOH) and gasification-DME). The combined processes were simulated using oxygen as a gasifying agent and the oil palm trunk, the agricultural waste generated from the palm oil industry, as feedstock. The gasification-MeOH process offered a higher amount of valuable product (methanol) and released a larger amount of CO2 . The energy analysis indicated the two biomass conversion processes were exothermic process. The gasification-DME process presented a higher biomass conversion efficiency of 59.5% compared to 47.6% of the gasification-MeOH. The pinch analysis of gasification-MeOH and the gasification-DME processes indicated threshold pinch that required only cold utility of 0.5542 kW and 0.7258 kW, respectively. Regarding the economic aspect, the two processes were still not economically feasible, and the methanol and DME prices and the project lifetime influenced their economic performance. However, due to the high product price, the gasification-DME process was approximately 7% more economically feasible than the gasification-MeOH process.